The Sectoral Trade Losses from Financial Crises - Atsebi, Jean-Marc (IMF Working Papers; Working Paper ;, 2021)
The "Great Trade Collapse" triggered by the 2008-09 crisis calls for a careful assessment of the trade losses from financial crises. We adopt a more detailed perspective by looking at the response of different types of trade (i.e. agricultural, mining, and manufactured goods, and services) following various types of financial crises (i.e. debt, banking, and currency crises). Estimations performed on the 1980-2018 period using a combination of impact assessment and local projections to capture a causal dynamic effect running from financial crises to the trade activity show that the collapse of total trade is long-lasting and mainly driven by the fall of manufacturing and to some extent services trade. These causal effects are found to operate through three channels: a structural, a demand-side, and a supply-side channel. By contributing to the understanding of the trade effects of financial crises, our analysis provides insightful support for the design and implementation of policies aimed at coping with these effects.